Prevalence of malarial recurrence and hematological alteration following the initial drug regimen: a retrospective study in Western Thailand - Manas Kotepui; Chuchard Punsawad; Kwuntida Uthaisar Kotepui; Voravuth Somsak; Nuoil Phiwklam; Bhukdee PhunPhuech (BMC, 2019)
Abstract Background The hematological changes following the initial drug regimen has been poorly understood in Thailand. This study was designed to determine the prevalence of malaria parasite recurrence and hematological alteration of patients during the initial drug regimen. Methods A retrospective study was conducted at Phop Phra Hospital, Tak Province, located in northwestern Thailand. All data from patients who were diagnosed with Plasmodium spp. infection - including types of Plasmodium spp., clinical characteristics, and hematological parameters - were retrieved and analyzed. Results The results demonstrated that during years 2012-2018, 95 out of 971 patients (9.78%) were infected with malaria two or more times. The gender, nationality, symptom of headache, type of Plasmodium spp., and career of each patient were associated with recurrence (P-value< 0.05). Among patients treated with malarial drug, the leukocyte count and red cell distribution width (RDW) were significantly changed when compared to untreated patients with recurrence (P-value< 0.05). Conclusion This study indicated the high prevalence of malarial recurrence in Tak Province, Western Thailand, and its relationship to certain characteristics of individuals. Patients who were treated with antimalarial drugs exhibited leukocyte and RDW changes following the initial drug regimen. This data could be useful for prompt detection, treatment, and prevention of malarial recurrence in endemic areas of Thailand.